Partnerships, imperfect monitoring and outside options: Theory and experimental evidence - Paolo Crosetto; Alexia Gaudeul; Gerhard Riener (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2012)
We study theoretically and experimentally a two-person partnership game whereby agents only see the uncertain outcome of their joint effort but not how much the other agent contributed to it. The model combines problems of free-riding present in public good production and in teams with imperfect monitoring. We analyse effort and exit behaviour conditional on subjects' beliefs over the action taken by their partners and consider the effect of the availability and profitability of outside options. Our subjects do not adapt effort as a response to changes in their beliefs about the effort of their partner. Subjects display aversion for team work by exiting the partnership even when they believe their partner exerts sufficient effort to sustain it. Higher outside options do not either motivate or discourage effort in joint work but rather result in not only inefficient but also irrational breakdown in partnerships. Overall, social welfare decreases as the incentive to exit increases.
Keywords: D82; H41; 330; Imperfect monitoring; outside options; partnerships; public good production; repeated games; teams; Arbeitsgruppe; Arbeitsleistung; Kontrolle; Trittbrettfahrerverhalten; Wiederholte Spiele; Test